When Should Entrepreneurs Expedite or Delay Opportunity Exploitation? - CHOI, Young Rok (Institutional Knowledge at Singapore Management University, 2008)
We theorize on the performance implications of the timing at which entrepreneurs stop exploring their business opportunities and start exploiting them. Using an optimal-stopping approach, we characterize the time when exploitation should begin based primarily on when an entrepreneur's ignorance has been sufficiently reduced through knowledge accumulation. This “ignorance threshold” captures a tradeoff between the time needed to increase legitimacy and the necessity to act now to minimize competition. Changes in legitimacy and competition are based on how entrepreneurs manage their knowledge (tacit versus explicit) under differing degrees of novelty for the business opportunity. These changes, in turn, impact the performance and timing of opportunity exploitation.